Look who's talking ebook - Blabey, Aaron (The Bad Guys, 2023)
Now a major motion picture! "I wish I'd had these books as a kid. Hilarious!" — Dav Pilkey, creator of Captain Underpants and Dog Man They may look like Bad Guys, but these wannabe heroes are doing good deeds... whether you like it or not in this New York Times bestselling illustrated series. Forget what you know. This book changes everything. Someone's found her voice and she has A LOT to tell you. Take a deep breath, hermano, it's the 18th installment of THE BAD GUYS!